Norway : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2007)
This Selected Issues paper analyzes core and idiosyncratic inflation in Norway. The paper provides estimates of underlying inflation, using a statistical technique to decompose inflation and a measure of core inflation into 'common' and 'idiosyncratic' components. It finds that overall inflation is not far from its underlying value, as estimated by the common component, while core inflation is below its underlying value. The paper also considers medium-term and long-term fiscal policy in light of high oil prices and the prospect of substantial increase in pension outlays.